2014
DOI: 10.1007/s13280-014-0571-2
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of newspaper coverage of water issues in Australia during 1843–2011

Abstract: News accounts both reflect and influence public opinion through their noted 'agenda-setting' capability. We examined newspaper articles in Australia's The Sydney Morning Herald from 1843 to 2011 to observe the evolution of media coverage on water issues related to water resources management. The results showed that water supply-related articles have dominated the reporting of water issues since 1843. This emphasis is reflected in the institutions involved and their related policy/management initiatives, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 32 publications
(34 reference statements)
6
42
0
Order By: Relevance
“…This supports a previous study suggesting limited short-term influence of news media reporting on a water reuse proposal (van Vuuren, 2009). Though it has been suggested that media framing contributes to polarizing attitudes towards water management proposals (Wei et al, 2015), this may be set by longer-term agendas (Carvalho & Burgess, 2005;Leong, 2010). Longer-term media agendas may, therefore, challenge single media communication events of IPR scheme proposals and supersede more issue-specific frames if they shape people's perceptions of more general issues such as population growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports a previous study suggesting limited short-term influence of news media reporting on a water reuse proposal (van Vuuren, 2009). Though it has been suggested that media framing contributes to polarizing attitudes towards water management proposals (Wei et al, 2015), this may be set by longer-term agendas (Carvalho & Burgess, 2005;Leong, 2010). Longer-term media agendas may, therefore, challenge single media communication events of IPR scheme proposals and supersede more issue-specific frames if they shape people's perceptions of more general issues such as population growth.…”
Section: Discussionmentioning
confidence: 99%
“…Media framing may contribute to polarizing community attitudes towards water management (Wei, Wei, Western, Skinner, & Lyle, 2015). Research has focused on content analysis of media reporting of water management Xiong, Wei, Zhang, & Wei, 2016), and specifically water reuse (Leong, 2010;van Vuuren, 2009), to identify framing perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…As the name suggests, it makes use of a media monitor to retrieve information on droughts and related topics world‐wide. For Australia, newspaper articles covering water‐related issues have been collected within a research initiative …”
Section: What Are the Current Practices For Drought Impact Monitoring?mentioning
confidence: 99%
“…For example, Chen et al () validated their model results using newspaper articles collected from The New York Times. Gonzales and Ajami () validated their model results using the relative number of Google searches for the term “California drought.” Elshafei et al () validated their results using water‐related newspaper articles in Australia (Wei et al, ). In our model, the evolution of community sensitivity is partially (if not completely) confirmed by newspaper articles in the People's Daily (Chinese mainstream newspaper), which reflect evolution of human perceptions of water shortage and other anecdotal evidence that represents human response behaviors in respect of water resources management (see section for details).…”
Section: Model and Datamentioning
confidence: 92%